Impact of prolonged use of adjuvant tocolytics after cervical cerclage on late abortion and premature delivery. (31st December 2023) - Zhao, Li-Rong; Lu, Shu-Jing; Liu, Qing; Yu, Ying-Chun; Xiao, Li
Abstract: We evaluated the impact of cervical cerclage combined with one or more uterine contraction inhibitors in persistent inhibition of uterine contraction for the treatment of late abortion and premature delivery. This retrospective case series study analysed the medical data of 58 patients who underwent cervical cerclage for cervical insufficiency and simultaneously received one or more uterine contraction inhibitors (indomethacin, ritodrine, and atosiban) and magnesium sulphate at the Zibo Maternal and Child Health Hospital between January 2019 and December 2020.Patients are normal pregnancy who received cervical cerclage without complications. The rate of successful treatment was 74.14% (43/58). The prolonged gestation duration was 16.42 ± 7.84 weeks, and the average delivery gestational age was 35.91 ± 5.16 weeks. The longest duration of treatment with a uterine contraction inhibitor or inhibitors in combination or with magnesium sulphate alone was 15.34 ± 13.16 days, and nine cases developed adverse reactions. Persistent uterine contraction inhibition after cervical cerclage could prolong pregnancy and improve pregnancy outcomes. Impact statement: What is already known on this subject? A crucial reason for treatment failure of cervical cerclage is that uterine contraction was not effectively inhibited. What do the results of this study add? Persistent inhibition of uterine contraction after cervical cerclage prolonged pregnancy duration, increased gestational age at delivery, and improved pregnancy outcomes. What are the implications of these findings for clinical practice and/or further research? This study may provide a clinical basis for prolonging gestational age, preventing late abortion and premature delivery, and improving the survival rate and quality of life of premature infants.